Acoustical investigation of open-plan offices in green building: Simulation experiment - Che Din, Nazli; Abd Jalil, Nurul Amira; Keumala, Nila; Abdul-Razak, Asrul Sani (2014)
The authors have previously reported on the measurement results from the investigation and evaluation done on the acoustical performance of open-plan offices in green buildings in Malaysia. This research uses the results from field measurements for verification on the optimum modeling process for two existing open-plan office in term of calculation time and accuracy of the simulation. Two models of open-plan office layout were constructed in four different level of model detailing utilizing 3D modeling tool. Using ODEON Room Acoustic Simulation Software, the authors examined the effects of the geometrical properties to identify the appropriate model setting for further simulation process. The simulated results of two acoustical parameters; reverberation time (RT) and speech transmission index (STI) for each model setup are then compared between each other, and further compared with field measurement results. The study concludes that the modeling process in term of number of surfaces is affecting the acoustical parameters. The discrepancy of simulated RT and STI data between model setup will be discussed.